Buya HAMKA character education: Understanding traditional values in learning science in the 21st century digital era - Yusuf, Irfan; Kuswandi, Dedi (Journal of Research in Instructional, 2023)
This research aims to analyze the values of character education in Buya HAMKA's thinking and their relevance to science learning in the digital era of the 21st century. This research method uses historical research methods with literature study. The technique used to analyze data is qualitative descriptive analysis. The research results show that the traditional values of character education, from the perspective of Buya HAMKA, are still very relevant to science learning in the digital era of the 21st century. The research results also obtained an educational scientific edifice according to Buya HAMKA. Buya HAMKA's way of thinking contains the principles of character education. Buya HAMKA's works on character education contain various forms of character education values, including sincerity (ikhlas), justice, caring (rahmatan lil alamin), perseverance (istiqamah), independence, respect (adab), and cooperation. The concept of character education presented by Buya HAMKA is still very relevant in the digital era of the 21st century. It can be linked to character values that can be developed in science learning. Even though the characteristics of the 21st century generation are different from those of the past, the principles of character education applied by Buya HAMKA can be applied to individuals from all generations.